Cultural histories of India
1 online resource.
Keywords: This book explores the social and cultural histories of India, focusing on cultural encounters and representations of subaltern communities from the seventeenth to the twenty-first century. Examining cultural encounters between Europeans and Indians during the precolonial and colonial periods, the book analyzes European, especially English, efforts to exoticize or investigate the social practices of the Other. It also presents the culturally conditioned Indian subject's perspective on Europe and the imperial society. The book engages with narratives of suppressed movements of tribals and dalits, of erosion of the culture and history of ancient communities, and recovers the local narratives of marginalized groups in Andaman and Malabar, which get superseded by the larger narrative of nation-building. Often relying on oral history instead of printed material and sociological fieldwork, the alternate histories are presented through unconventional, literary or semi-literary genres like travel narratives, fiction, films, and songs, thus presenting an alternative interpretation to the central narrative of the progress of mainstream India. Representing cultural history and the view from below, the book shifts its focus from the conventional historiography associated with political history and will be of interest to academics working in the field of cultural studies, the historiography of India, South Asian Studies and an interdisciplinary audience in history, sociology, literature, media, and English studies.